Human basophils are a source of ‐ and are differentially activated by ‐ IL‐31. Issue 4 (1st February 2017) - Raap, U.; Gehring, M.; Kleiner, S.; Rüdrich, U.; Eiz‐Vesper, B.; Haas, H.; Kapp, A.; Gibbs, B. F.
Summary: Background: Basophils are important effector cells involved in the pathogenesis of inflammatory skin diseases including chronic urticaria which is associated by increased IL‐31 serum levels. So far the effects of IL‐31 on human basophils are unknown. Objective: To analyse the functional role of IL‐31 in basophil biology. Methods: IL‐31 expression was evaluated in skin samples derived from chronic spontaneous urticaria patients. Oncostatin M receptor (OSMR), IL‐31 receptor A (RA) and IL‐31 protein expressions were analysed on human basophils from healthy donors. Basophil responses to IL‐31 were assessed for chemotaxis, externalization of CD63 and CD203c as well as the release of histamine, IL‐4 and IL‐13. Results: IL‐31RA and OSMR were expressed on human basophils. IL‐31 was strongly expressed in the skin of patients with chronic spontaneous urticaria and was released from isolated basophils following either anti‐IgE, IL‐3 or fMLP stimulation. IL‐31 induced chemotaxis and the release of IL‐4 and IL‐13 which was specifically inhibited by anti‐IL‐31RA and anti‐OSMR. Conversely, IL‐31 had no effect on CD63 and CD203c externalization or histamine release. Conclusions and Clinical Relevance: Human basophils are a source of –and are activated by – IL‐31 with the release of pro‐inflammatory cytokines and the induction of chemotaxis indicating an important novel function of IL‐31 in basophil biology.